The perception of family farmers of Programa de Aquisição de Alimentos (PAA) on the meaning of being part of PAA and their understanding of concepts related to food, nutrition and health - Batista, Lucimar Moreira Guimarães; Ribeiro, Sônia Machado Rocha; Santos, Ricardo Henrique Silva; Araújo, Raquel Maria Amaral; Ribeiro, Andréia Queiroz; Priore, Sílvia Eloiza; Lúcia, Ceres Mattos Della; Lana, Rogério de Paula; Gasparoni, Gisely Peron (Saúde e Sociedade, 2016)
Family agriculture has a recognized economic, environmental and social potential, which in recent years has been prestigious and strengthened by government programs that encourage the production and processing of their products, thus Food and Nutrition Security actions can be implemented, increasing the availability of food and the variability of nutrients to the population, favoring the their marketing at local and regional levels, contributing to healthy eating habits and thus improving the quality of food. The Programa de Aquisição de Alimentos (PAA) [Food Acquisition Program] was established by the article 19 of Law nº 10.696 in 2003 as one of the actions of the Programa Fome Zero [Zero Hungry Program] your main goal is the strengthening of family agriculture. The objective of this study was to identify the perceptions of farmers on the meaning of being part of the PAA and their understanding of concepts related to food, nutrition and health through a qualitative research. The results of this study were greater access to information such as health, food, forms of production and management, economics, rights and duties, among others; improved income and family investments; improved self-esteem/self-worth and stimulate the interaction of family farmers. In this context, it is necessary that the PAA increasingly become an empowering tool of agriculture family in the health care and Food and Nutrition Security permanently as proposed in his law of creation.